2003
DOI: 10.1682/jrrd.2003.07.0293
|View full text |Cite
|
Sign up to set email alerts
|

Social integration and life and family satisfaction in survivors of injury at 5 years postinjury

Abstract: Abstract-This study assessed the relationship of social integration (SI) to life satisfaction and family satisfaction among survivors 5 years after injury. Thirty-four matched pairs of injured patients were interviewed by telephone 60 months after initial discharge from the acute care setting. Respondents were matched according to sex, race, education, injury severity, and employment status before comparing high and low socially integrated persons on measures of family and life satisfaction. High and low SI gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
3
13
0
5
Order By: Relevance
“…Social integration, which includes both the number of persons in an individuals' social network and satisfaction with the amount of time spent with others, is a vital component of life satisfaction for people in the general population, and there is an increasing body of evidence suggesting this is also true and perhaps even more so, for those who have had a brain injury (Lo Bello et al, 2003). Social integration in the community can be seriously compromised following ABI primarily because of cognitive and emotional/behavioural changes that have been shown to be challenges for the individuals' social networks (Brown, Gordan, & Spielman, 2003;Zencius & Wesolowski, 1999).…”
Section: Impact Of Abi On Community Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Social integration, which includes both the number of persons in an individuals' social network and satisfaction with the amount of time spent with others, is a vital component of life satisfaction for people in the general population, and there is an increasing body of evidence suggesting this is also true and perhaps even more so, for those who have had a brain injury (Lo Bello et al, 2003). Social integration in the community can be seriously compromised following ABI primarily because of cognitive and emotional/behavioural changes that have been shown to be challenges for the individuals' social networks (Brown, Gordan, & Spielman, 2003;Zencius & Wesolowski, 1999).…”
Section: Impact Of Abi On Community Integrationmentioning
confidence: 99%
“…Rehabilitation specialists working to increase an individual's level of social integration may expect greater post-injury adjustment to be reflected in greater life satisfaction and family satisfaction (Lo Bello et al, 2003).…”
Section: Impact Of Abi On Community Integrationmentioning
confidence: 99%
“…Testa et al [6] suggest that about one third of family relationships can be described as unhealthy at follow-up. LoBello et al [7] observed that the family also experiences a steadily shrinking social network, not just the individual with TBI. Gan et al [8] and Riley [9] found high levels of stress in caretakers, which was even more prominent for persons who had diminished social support.…”
Section: Introductionmentioning
confidence: 99%
“…Hutchinson et al (2003) demonstrated the role of leisure in the coping process following traumatic injury. LoBello et al (2003) showed that social integration was linked to greater general life satisfaction for people with TBI. They stated that the quality of life after the injury was more related 'to a healthy psychological functioning rather than the degree of physical impairment' (298).…”
Section: Role Of Leisurementioning
confidence: 99%